2011
DOI: 10.1016/j.micinf.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the underlying mechanism of resistance to Ascaris infection

Abstract: The generative mechanism(s) of predisposition to Ascaris infection are currently unknown.While many factors play a role in interindividual infection intensity, much focus has been placed on the host's immunological response to infection and the underlying genetics. The present review describes the research conducted that has examined various immunological parameters and genetic factors that may play a role in resistance to ascariasis. We also discuss the contribution that animal models have made to our underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Host genetics ultimately determines susceptibility or resistance to parasite infection through innate or acquired immunity (60). Therefore, the role of genetic factors and immunological parameters in predisposition to infection with helminths was recently emphasized (61), and the relevance of these observations to Toxocara sp. infection should be explored further.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Host genetics ultimately determines susceptibility or resistance to parasite infection through innate or acquired immunity (60). Therefore, the role of genetic factors and immunological parameters in predisposition to infection with helminths was recently emphasized (61), and the relevance of these observations to Toxocara sp. infection should be explored further.…”
Section: Risk Factorsmentioning
confidence: 99%
“…SNPs at two genes within the last of these regions, LIG4 and TNFSF13B, have shown associations with levels of IgG and IgE against Ascaris in a Colombian sample, suggesting that they could affect susceptibility to infection by promoting a protective humoral response against the parasite [86]. Candidate gene association studies of Ascaris infection intensity have shown significant results not only for IL13 [75] and STAT6 [68,75], as previously discussed, but also for IFNG [75]and ADRB2 (located in the 5q31-q33 region) [87] loci [6]. Recently, a large (N = 1353) candidate gene association study was conducted in Brazil, and showed that IL10 SNPs play a role in susceptibility to current and chronic infection with both A. lumbricoides and T. trichiura.…”
Section: Soil-transmitted Helminth Diseasesmentioning
confidence: 57%
“…Actually, for many parasitic diseases, a heritable component has been demonstrated. Evidence has been gained with a variety of approaches, including twin studies, observation of familial clustering, pedigree-based variance component analysis and segregation analysis, and studies of ethnic groups that share the same environmental exposure but show different susceptibilities [2][3][4][5][6][7][8][9][10]. Although parasitic diseases are clearly of multifactorial origin, the genetic architecture underlying susceptibility varies, with two possible extremes being represented by malaria, in which the genetic component is more probably explained by the additive effect of many loci with small to modest penetrance [11], and Schistosoma infection, in which one major locus with high penetrance seems to be involved [12].…”
Section: Introductionmentioning
confidence: 99%
“…89 Infection elicits the production of cytokines, predominantly associated with a Th2-type response, and antibodies of all isotypes, particularly IgE and Ascaris-specific IgE. 90,91 These immunoglobulins do not seem to be protective; 92 rather, they reflect current or past infection.…”
Section: The Role Of Host Geneticsmentioning
confidence: 99%